Pengaruh Struktur Modal, Leverage dan Environmental Social Governance (ESG) terhadap Kinerja Perusahaan - Sari, Silvia; Sunandi, Elly Rahmalia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
One of the main objectives of a company is to improve performance in a sustainable manner. To achieve this, companies must be able to manage their financial structure and implement responsible business practices. This study aims to empirically examine the effect of capital structure, leverage, and Environmental Social Governance (ESG) on firm performance, both partially and simultaneously. This research was conducted by analyzing companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during the 2019 to 2023 period. The sample consisted of 8 companies selected using a purposive sampling technique. The data used in this study are secondary data in the form of financial reports and ESG reports. This study employed a panel data regression method with analysis conducted using Eviews 12 software. The results of the study show that the best-fit model is the Common Effect Model (CEM). The findings reveal that capital structure, leverage, and ESG simultaneously influence firm performance. Partially, ESG does not have a significant effect on firm performance, leverage has no significant effect, and capital structure also does not have a significant effect on firm performance.